Low-viscosity light-cured nitride ceramic slurry as well as preparation method and application thereof
By using nitride ceramic composite powder and surface modifier LMY in photocured nitride ceramic slurry, combined with the preparation of polyacrylates and dispersants, the problem of difficult to take into account solid content, viscosity and photocuring depth is significantly improved The processability and performance of nitride ceramic slurry are suitable for 3D printing of complex structural parts.
Patent Information
- Application Number
- CN202411451554.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-14
AI Technical Summary
The existing photocured nitride ceramic slurry is difficult to take into account the solid content, viscosity and photocuring depth, especially the long-term stability, which affects the preparation processability and performance of complex structural parts.
Low viscosity photocuring nitride ceramic slurry, whose components include nitride ceramic composite powder, polyacrylate, first dispersant DC, stabilizer and photoinitiator, and are adjusted by ball milling treatment and the use of the surface modifier LMY. The refractive index difference and photocuring characteristics of the powder improve the curing depth and density.
It has achieved solid content ≥65wt.%, photocuring depth ≥60μm, viscosity ≤2500mPa·s and long-term stability improvement, significantly improving the processability and performance of nitride ceramic slurry, and is suitable for 3D for large-size complex structural parts. Print.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of photocured nitride ceramic materials, and in particular to a low-viscosity photocured nitride ceramic slurry and a preparation method and application thereof. Background Art
[0002] Nitride ceramics, such as AlN, BN, Si3N4 and other ceramic materials, have relatively low density, high toughness, high hardness, wear resistance, corrosion resistance, excellent electromagnetic properties, excellent thermal conductivity, strong resistance to thermal shock (heated to above 1000℃ in air, rapid cooling and rapid heating will not break), high strength below 1300℃, high chemical stability and non-toxicity, etc., and have been continuously valued by researchers at home and abroad, and are widely used in metallurgy, energy, machinery, aerospace, electronics, bioengineering and other fields, especially in aviation, aerospace, electronics and bioengineering. However, due to the inherent high melting point, high strength and high hardness of nitride ceramics, the difficulty of precise preparation of complex shaped special-shaped structural parts is greatly increased.
[0003] Compared with traditional processes, photocuring 3D printing technology does not require molds, has high material utilization, high structural accuracy and stable performance, and is very suitable for the preparation of complex structural devices. The quality and service performance of photocuring 3D printed ceramic components depend on the rheological properties of the ceramic slurry, the photocuring characteristics, the printing process, and the degreasing and roasting post-treatment process. The photocuring 3D printing molding technology of oxide ceramics such as Al2O3, SiO2, and ZrO2 is relatively mature and has been applied; but the photocuring 3D printing technology for non-oxide ceramics such as Si3N4 and SiC is still in research and development, and there are still some technical difficulties to overcome, especially the technical difficulties in the process control of nitride ceramic slurry have not been overcome: At an ultraviolet wavelength of 405nm, the refractive index of Si3N4 powder (2.0978) is greater than that of common oxide powders (such as SiO2-1.5571) and Al2O3-1.7555). The refractive index difference between Si3N4 ceramic powder and the slurry photosensitive resin medium is also large, resulting in a small curing depth of the ceramic slurry, which is difficult to meet the requirements of photocuring forming.
[0004] A method for surface oxidation treatment of Si3N4 ceramic powder has been proposed. A thin SiO2 shell is formed on the surface of Si3N4 powder particles by oxidation to increase the curing depth, and then a photocuring 3D printing method is used to manufacture Si3N4 parts with complex shapes. SiO2 has a low refractive index, which can reduce the refractive index difference between the surface of Si3N4 powder and photosensitive resin, and can reduce the ultraviolet light absorption rate of Si3N4 powder, and increase the penetration depth of incident light in Si3N4 ceramic slurry. However, the solid content of Si3N4 ceramic slurry is not high, which has an adverse effect on the strength of the formed green body and the density and mechanical properties of the ceramic after sintering. In addition, the formed SiO2 thin shell will reduce the sintering temperature, and also significantly reduce the mechanical properties, high temperature properties and electromagnetic properties of Si3N4 ceramic parts. Stability.
[0005] Some researchers have also proposed using Al2O3-Y2O3 to coat Si3N4 based on the fact that Al2O3 and Y2O3 are commonly used sintering aids for Si3N4 ceramics and their refractive indices are smaller than that of Si3N4. On the one hand, this can reduce the absorption of ultraviolet light by Si3N4 powder and reduce the refractive index difference between Si3N4 powder and photosensitive resin, thereby improving the photocuring performance of Si3N4 powder; on the other hand, as a sintering aid, it can optimize the sintering densification process of Si3N4, thereby improving the mechanical properties of Si3N4 ceramics; however, this scheme has problems with the long-term stability of the slurry, the large dielectric constant and tangent loss of the fired ceramics.
[0006] In summary, the existing photocurable nitride ceramic slurry has the technical difficulty of taking into account the solid content, viscosity, photocuring depth and long-term stability. Summary of the invention
[0007] In order to solve the deficiencies of the prior art mentioned in the above background technology, the present application provides a low-viscosity photocurable nitride ceramic slurry, and its technical solution is as follows: The low-viscosity photocurable nitride ceramic slurry provided in the present application comprises components including nitride ceramic composite powder, polyacrylate, a first dispersant DC, a stabilizer and a photoinitiator; wherein the mass ratio of the nitride ceramic composite powder, polyacrylate, the first dispersant DC, the stabilizer and the photoinitiator is (65-75): (15-30): (1.0-5.0): (5.0-10.0): (0.5-1.5); the components of the nitride ceramic composite powder comprise nitride ceramic powder, a surface modifier LMY and a second dispersant DC; wherein the mass ratio of the nitride ceramic powder, the surface modifier LMY and the second dispersant DC is (85-95): (5.0-10): (2.0-5.0).
[0008] In some embodiments, the photocurable nitride ceramic slurry is prepared by ball milling and mixing nitride ceramic composite powder, polyacrylate, a first dispersant DC, a stabilizer, and a photoinitiator in a mass ratio of (65-75): (15-30): (1.0-5.0): (5.0-10.0): (0.5-1.5); wherein the nitride ceramic composite powder is prepared by mixing nitride ceramic powder, a surface modifier LMY powder, and a second dispersant DC in a mass ratio of (85-95): (5.0-10): (2.0-5.0).
[0009] In some embodiments, the polyacrylate is a mixture of at least two of 1,6-hexanediol diacrylate, polysiloxane acrylate, trimethylolpropane triacrylate, and ditrimethylolpropane tetraacrylate in any proportion; the stabilizer is KH570; and the photoinitiator is TPO.
[0010] In some embodiments, the particle size of the nitride ceramic powder is 0.5 to 5 μm; the first dispersant DC and the second dispersant DC are organic phosphates; the surface modifier LMY is a Li2O-Mg-Y2O3 ternary eutectic oxide, which is prepared by mixing lithium oxide, magnesium oxide, and yttrium oxide in a proportion to form a ternary eutectic oxide.
[0011] In some embodiments, the preparation process of the surface modifier LMY is: weigh lithium oxide powder, magnesium oxide powder and yttrium oxide powder according to the eutectic ratio, add them to an ethanol solvent, and stir and disperse to obtain a mixture M; ball mill the mixture M to obtain a uniformly dispersed slurry; evaporate the ethanol solvent in the slurry to obtain the powdered surface modifier LMY.
[0012] In some embodiments, the ball milling treatment conditions are ball milling at a rate of 180-300 r / min for 6-10 hours; volatilizing the ethanol solvent in the slurry under normal temperature and atmospheric environment, or evaporating and removing the ethanol solvent in an oven below 50-60°C to obtain the powdered surface modifier LMY.
[0013] The present application also provides a method for preparing the low-viscosity photocurable nitride ceramic slurry as described above, which comprises the following steps: Weigh the raw material components according to the formula ratio, add the stabilizer, the first dispersant DC, and the photoinitiator to the polyacrylate in sequence while stirring, and stir and mix evenly to obtain a uniformly dispersed photosensitive resin system; Weighing nitride ceramic powder, surface modifier LMY powder, and second dispersant DC according to the formula mass ratio; adding nitride ceramic powder, surface modifier LMY powder, and second dispersant DC into ethanol solvent while stirring and dispersing them uniformly to obtain pre-dispersed slurry; evaporating the ethanol solvent in the pre-dispersed slurry to obtain ceramic powder; sieving the ceramic powder to obtain the nitride ceramic composite powder; Adding the nitride ceramic composite powder to the photosensitive resin system while stirring, stirring and dispersing evenly to obtain a preliminarily homogenized nitride ceramic slurry; The preliminarily homogenized nitride ceramic slurry is ball-milled to obtain the light-cured nitride ceramic slurry.
[0014] In some embodiments, the raw material components are weighed according to the formula ratio, and the stabilizer, the first dispersant DC, and the photoinitiator are sequentially added to the polyacrylate while stirring, and stirred and mixed evenly for a stirring time of not less than 0.5 h to obtain a uniformly dispersed photosensitive resin system; Weigh the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC according to the formula mass ratio; add the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC into the ethanol solvent while stirring, and stir at a rate of not less than 200 r / min for 2 to 4 hours to obtain a pre-dispersed slurry; evaporate the ethanol solvent in the pre-dispersed slurry at a heating temperature of 50 to 60° C. to obtain a ceramic powder; pass the ceramic powder through a 200-mesh sieve to obtain the nitride ceramic composite powder; Adding the nitride ceramic composite powder to the photosensitive resin system while stirring, stirring at a rate of not less than 100 r / min for 2 hours to obtain a preliminarily homogenized nitride ceramic slurry; The preliminarily homogenized nitride ceramic slurry is ball-milled at a rate of 200 to 300 r / min for 10 to 24 hours to obtain the light-cured nitride ceramic slurry.
[0015] The present application also provides the use of the above-mentioned photocurable nitride ceramic slurry in the preparation of AlN nitride ceramic parts, BN nitride ceramic parts, and Si3N4 nitride ceramic parts.
[0016] In some embodiments, during the preparation of AlN nitride ceramic parts or BN nitride ceramic parts or Si3N4 nitride ceramic parts, a photocuring ultraviolet light source is used to photocure the photocuring nitride ceramic slurry to obtain a photocured nitride ceramic body; and the photocured nitride ceramic body is degreased and sintered in sequence to obtain a nitride ceramic part; wherein the wavelength of the photocuring ultraviolet light source is 355 to 405 nm.
[0017] Based on the above, compared with the prior art, this application has the following beneficial effects: The low-viscosity photocurable nitride ceramic slurry provided in this application has a solid content of ≥65wt.%, a photocuring depth of ≥60μm, a viscosity of ≤2500mPa∙s, and a viscosity change rate of ≤10% and a sedimentation rate of ≤20% after the slurry is naturally left to stand for 200h. It solves the technical difficulties of the traditional photocurable nitride ceramic slurry in terms of solid content, viscosity, photocuring depth, and long-term stability, and significantly improves the processability of nitride ceramic slurry photocuring 3D printing of large-sized complex structural parts. The high-precision, high-performance large-scale complex structure nitride ceramic products prepared by the nitride ceramic slurry can be better applied in aviation, aerospace, medical and industrial fields.
[0018] Other features and beneficial effects of the present application will be described in the following description, and partly become apparent from the description, or understood by practicing the present application. The purpose and other beneficial effects of the present application can be achieved and obtained by the structures specifically pointed out in the description and claims. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described in combination with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments; the technical features designed in different implementation modes of the present application described below can be combined with each other as long as they do not conflict with each other; based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] In the description of this application, it should be noted that all terms (including technical terms and scientific terms) used in this application have the same meanings as those generally understood by ordinary technicians in the field to which this application belongs, and cannot be understood as limitations on this application; it should be further understood that the terms used in this application should be understood to have meanings consistent with the meanings of these terms in the context of this specification and in the relevant fields, and should not be understood in an idealized or overly formal sense, unless explicitly defined in this application.
[0021] The present application provides an operational example of a method for preparing a low-viscosity photocurable nitride ceramic slurry, and the specific steps are as follows: Step 1: Lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder are weighed according to the eutectic ratio (i.e., the ratio of forming a ternary eutectic oxide), and added together into an ethanol solvent for stirring and dispersion; then transferred into a planetary ball mill for ball milling at a rate of 180-300 r / min for 6-10 hours to obtain a uniformly dispersed slurry; thereafter, the ethanol solvent is volatilized in an atmospheric environment or evaporated and removed in an oven below 50-60°C to obtain a surface modifier LMY powder (i.e., Li2O-Mg-Y2O3 ternary eutectic oxide) for standby use.
[0022] Step 2 Weigh the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC according to the formula mass ratio; add the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC into the ethanol solvent while stirring, and stir at a rate of not less than 200 r / min for 2 to 4 hours to obtain a pre-dispersed slurry; evaporate the ethanol solvent in the pre-dispersed slurry at a heating temperature of 50 to 60° C. to obtain a ceramic powder; pass the ceramic powder through a 200-mesh sieve to obtain the nitride ceramic composite powder; The mass ratio of the nitride ceramic powder, the surface modifier LMY, and the second dispersant DC is (85-95): (5.0-10): (2.0-5.0). The particle size of the nitride ceramic powder is 0.5-5 μm; and the second dispersant DC is an organic phosphate.
[0023] Step 3: The raw material components are weighed according to the formula ratio, and the stabilizer, the first dispersant DC, and the photoinitiator are added to the polyacrylate in sequence while stirring, and stirred to mix evenly for a stirring time of not less than 0.5 h to obtain a uniformly dispersed photosensitive resin system.
[0024] Step 4 Adding the nitride ceramic composite powder to the photosensitive resin system while stirring, stirring at a rate of not less than 100 r / min for 2 hours to obtain a preliminarily homogenized nitride ceramic slurry; Among them, the mass ratio of nitride ceramic composite powder, polyacrylate, first dispersant DC, stabilizer and photoinitiator is (65-75): (15-30): (1.0-5.0): (5.0-10.0): (0.5-1.5).
[0025] The polyacrylate is a mixture of at least two of 1,6-hexanediol diacrylate, polysiloxane acrylate, trimethylolpropane triacrylate, and ditrimethylolpropane tetraacrylate in any proportion; the first dispersant is DC organic phosphate; the stabilizer is KH570, which is used to control the viscosity and long-term stability of the ceramic slurry; and the photoinitiator is TPO.
[0026] Step 5 The preliminarily homogenized nitride ceramic slurry is transferred to a planetary ball mill and ball-milled at a rate of 200 to 300 r / min for 10 to 24 hours to obtain a light-cured nitride ceramic slurry with low viscosity, high ceramic yield and long-term stability.
[0027] In addition, the present application also provides an operational example of the application method of the above-mentioned photocurable nitride ceramic slurry in the preparation of AlN, BN, and Si3N4 nitride ceramic parts: In the process of preparing AlN, BN, and Si3N4 nitride ceramic parts, a photocuring ultraviolet light source is used to photocure the photocuring nitride ceramic slurry to obtain a photocuring nitride ceramic body. The photocuring nitride ceramic body is then degreased and sintered in sequence to obtain a nitride ceramic part; The wavelength of the ultraviolet light source used for photocuring is 355-405 nm.
[0028] The present invention provides the following examples and comparative examples to verify the effects of the present application: Example 1 The preparation process of this embodiment is as follows: Step 1: Lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder are weighed according to the eutectic ratio (i.e., the ratio of forming a ternary eutectic oxide), and added together into an ethanol solvent for stirring and dispersion; then transferred into a planetary ball mill for ball milling at a rate of 180 r / min for 10 hours to obtain a uniformly dispersed slurry; thereafter, the ethanol solvent is evaporated and removed in an oven below 50° C. to obtain a surface modifier LMY powder (i.e., Li2O-Mg-Y2O3 ternary eutectic oxide) for standby use.
[0029] Among them, lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic molar ratio of 2:5:3.
[0030] Step 2 Weigh the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC according to the formula mass ratio; add the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC into the ethanol solvent while stirring, and stir at a rate of 240r / min for 2h to obtain a pre-dispersed slurry; evaporate the ethanol solvent in the pre-dispersed slurry at a heating temperature of 50°C to obtain a ceramic powder; pass the ceramic powder through a 200-mesh sieve to obtain the nitride ceramic composite powder; Among them, the nitride ceramic powder uses silicon nitride ceramic powder with a particle size of 1 to 3 μm, with an amount of 1000g; the surface modifier LMY (a mixture of ternary eutectic oxides of lithium oxide (Li2O), magnesium oxide (MgO), and yttrium oxide (Y2O3)) is used in an amount of 60g; the second dispersant DC is an organic phosphate ester, with an amount of 30g.
[0031] Step 3: The raw material components were weighed according to the formula ratio, and the stabilizer, the first dispersant DC, and the photoinitiator were added to the polyacrylate in sequence while stirring, and the mixture was stirred evenly for 1.0 h to obtain a uniformly dispersed photosensitive resin system.
[0032] Step 4 Adding the nitride ceramic composite powder to the photosensitive resin system while stirring, stirring at a rate of 120 r / min for 2 hours to obtain a preliminarily homogenized nitride ceramic slurry; Among them, the amount of nitride ceramic composite powder is 700g, the amount of polyacrylate is 200g, which is a mixture of 1,6-hexanediol diacrylate and trimethylolpropane triacrylate in a mass ratio of 1:1; the first dispersant DC is organic phosphate, the amount is 30g, the stabilizer is KH570, the amount is 70g, and the photoinitiator is TPO, the amount is 10g.
[0033] Step 5 The preliminarily homogenized nitride ceramic slurry was transferred to a planetary ball mill and ball-milled at a rate of 200 r / min for 24 h to obtain a light-cured nitride ceramic slurry.
[0034] In the embodiment, the amount of ethanol solvent used is sufficient to fully immerse the raw materials, and the raw material components can be fully stirred and mixed in the solvent.
[0035] Example 2 The preparation process of this embodiment is as follows: Step 1: Lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder are weighed according to the eutectic ratio (i.e., the ratio of forming a ternary eutectic oxide), and added together into an ethanol solvent for stirring and dispersion; then transferred into a planetary ball mill for ball milling at a rate of 300 r / min for 6 hours to obtain a uniformly dispersed slurry; thereafter, the ethanol solvent is evaporated and removed in an oven below 60°C to obtain a surface modifier LMY powder (i.e., Li2O-Mg-Y2O3 ternary eutectic oxide) for standby use.
[0036] Among them, lithium oxide (Li2O) powder, magnesium oxide (MgO) powder and yttrium oxide (Y2O3) powder were weighed according to the eutectic molar ratio of 2:5:3.
[0037] Step 2 Weigh the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC according to the formula mass ratio; add the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC into the ethanol solvent while stirring, and stir at a rate of 300 r / min for 4 hours to obtain a pre-dispersed slurry; evaporate the ethanol solvent in the pre-dispersed slurry at a heating temperature of 60° C. to obtain a ceramic powder; pass the ceramic powder through a 200-mesh sieve to obtain the nitride ceramic composite powder; Among them, the nitride ceramic powder uses silicon nitride ceramic powder with a particle size of 1 to 3 μm, with an amount of 1000g; the surface modifier LMY (a mixture of ternary eutectic oxides of lithium oxide (Li2O), magnesium oxide (MgO), and yttrium oxide (Y2O3)) is used in an amount of 100g; the second dispersant DC is an organic phosphate ester, with an amount of 50g.
[0038] Step 3: The raw material components were weighed according to the formula ratio, and the stabilizer, the first dispersant DC, and the photoinitiator were added to the polyacrylate in sequence while stirring, and the mixture was stirred evenly for 3.0 hours to obtain a uniformly dispersed photosensitive resin system.
[0039] Step 4 Adding the nitride ceramic composite powder to the photosensitive resin system while stirring, stirring at a rate of 180 r / min for 2 hours to obtain a preliminarily homogenized nitride ceramic slurry; Among them, the amount of nitride ceramic composite powder is 700g, the amount of polyacrylate is 300g, which is prepared by mixing 1,6-hexanediol diacrylate, polysiloxane acrylate and ditrimethylolpropane tetraacrylate in a mass ratio of 1:0.5:1.5; the first dispersant DC is organic phosphate, the amount of which is 40g, the stabilizer is KH570, the amount of which is 80g, and the photoinitiator is TPO, the amount of which is 15g.
[0040] Step 5 The preliminarily homogenized nitride ceramic slurry was transferred to a planetary ball mill and subjected to ball milling treatment at a rate of 300 r / min for 10 h to obtain a light-cured nitride ceramic slurry.
[0041] In the embodiment, the amount of ethanol solvent used is sufficient to fully immerse the raw materials, and the raw material components can be fully stirred and mixed in the solvent.
[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that: The acrylate is 1,6-hexanediol diacrylate; the stabilizer is BYK410; the first dispersant DC and the second dispersant DC are polyacrylate KOS110; The ratio of nitride ceramic composite powder, acrylate, first dispersant DC, stabilizer and photoinitiator is 600g:320g:30g:40g:10g.
[0043] The other steps and preparation conditions are consistent with those in Example 1.
[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that the acrylate is 1,6-hexanediol diacrylate. The other steps and preparation conditions are the same as those in Example 1.
[0045] Comparative Example 3 The difference between this comparative example and Example 1 is that BYK410 is used as the stabilizer, and the other steps and preparation conditions are the same as those of Example 1.
[0046] Comparative Example 4 The difference between this comparative example and Example 1 is that the first dispersant DC and the second dispersant DC are polyacrylate KOS110, and the other steps and preparation conditions are the same as those in Example 1.
[0047] Comparative Example 5 The difference between this comparative example and Example 1 is that the ball milling process setting in step 5 is different, and the ball milling condition is ball milling at a rate of 150 r / min for 10 h.
[0048] The other steps and preparation conditions are consistent with those in Example 1.
[0049] The low-viscosity photocurable nitride ceramic slurries prepared in the examples and comparative examples were tested for their corresponding properties. The test results are detailed in Table 1: Table 1
[0050] The testing process and important parameters of the photocuring depth are as follows: add the prepared nitride ceramic slurry into the storage bin of the SLA-3D printing equipment, and set the printing parameters according to the laser power factor of 0.56-0.72, the scanning rate of 2000-3500mm / s, the single layer thickness of the material 50-60μm, and the cross-sectional size of the test piece model of 10mm×10mm. Start the printing system, lay 3-4 layers of material, and perform single-layer scanning and curing on the test piece at the rated laser output power; take out the cured single-layer test piece, clean off the slurry adhering to the surface of the test piece, and use a micrometer to measure the thickness of the test piece to obtain the photocuring depth of the slurry.
[0051] The test process and important parameters of sedimentation rate are as follows: in the atmosphere, room temperature, and light-proof environment, the prepared nitride ceramic slurry is placed in a clean, scaled transparent measuring cup, and left to stand for different time periods of 0h, 100h, 200h, and 300h, and 5.0-10.0g of slurry samples are taken at the same height from the liquid surface. The samples are placed in a clean and dry porcelain boat, and degreased in a N2 atmosphere at room temperature to 1000-1050℃, and the thermal weight loss rate is measured, and compared with the 0h slurry sample to convert the sample sedimentation rate.
[0052] From Table 1 we can see that: 1. The embodiment of the present application solves the technical problem of the solid content, viscosity, photocuring depth and long-term stability of the photocured nitride ceramic slurry by composite modification of the surface of the nitride ceramic powder. Among them, the ternary eutectic oxide (surface modifier LMY) in the nitride ceramic composite powder is used as a surface modifier to coat the nitride ceramic powder particles, reduce the refractive index of the nitride powder under ultraviolet light, and improve the photocurability of the slurry; at the same time, it is the best sintering aid for nitride ceramics such as silicon nitride and aluminum nitride, which can reduce the firing temperature and the difficulty of densification sintering, so that the density of the sintered product is significantly improved, and the fired ceramic has high thermal conductivity and strength, and the dielectric constant and tangent loss are controllable.
[0053] The low-viscosity photocured nitride ceramic slurry prepared in Example 1 of the present application has a solid content of ≥65wt.%, a photocuring depth of ≥60μm, a viscosity of ≤2500mPa∙s, and a viscosity change rate of ≤10% and a sedimentation rate of ≤20% after the slurry is naturally left to stand for 200h. It solves the technical problem that the solid content, viscosity, photocuring depth, and long-term stability of traditional photocured nitride ceramic slurry are difficult to balance, and significantly improves the processability of photocuring 3D printing of large-sized complex structures with nitride ceramic slurry. The high-precision, high-performance large-scale complex structure nitride ceramic products prepared by the nitride ceramic slurry can be better applied in aviation, aerospace, medical and industrial fields.
[0054] 2. From the comparison results of the comparative examples and the embodiments, it can be seen that: This application uses a specific multi-component composite acrylic resin combination. If only any one of 1,6-hexanediol diacrylate, polysiloxane acrylate, trimethylolpropane triacrylate, and ditrimethylolpropane tetraacrylate is used as the photosensitive resin system (comparative example), the 3D printing curing depth and strength cannot meet the requirements; The present application uses a specific type of stabilizer. If the conventional stabilizer BYK410 (comparative example) is used, it will cause the nitride slurry to agglomerate, which is not conducive to the stability of the slurry. This application uses a specific type of dispersant. If polyacrylate KOS110, polymer block copolymer dispersant KOS190, etc. are used, during the preparation process, the effect of this type of dispersant on the slurry viscosity and curing depth is not as good as that of the organic phosphate dispersant DC, and the obtained low-viscosity light-cured nitride ceramic slurry is not good; If the proportion of the nitride ceramic composite powder, the polyacrylate, the first dispersant DC, the stabilizer and the photoinitiator exceeds the range specified in this application, the solid content, the viscosity of the photocured nitride ceramic slurry and the curing depth are all damaged to varying degrees; If the ball milling before forming the slurry is not sufficient (the ball milling speed is lower than the limit value), the viscosity, photocuring depth, long-term stability, etc. of the obtained low-viscosity photocured nitride ceramic slurry will be poor.
[0055] It should be noted that: In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values.
[0056] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, but are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.
[0057] In addition, unless otherwise specified, the raw materials used may also be conventional commercial products in the art, or may be prepared by conventional methods in the art; that is, the reagents and instruments used in this embodiment are not indicated with information such as the manufacturer, and are all conventional products that can be purchased on the market.
[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A low-viscosity photocurable nitride ceramic slurry, characterized in that: Its components include nitride ceramic composite powder, polyacrylate, first dispersant DC, stabilizer and photoinitiator; Wherein, the mass ratio of nitride ceramic composite powder, polyacrylate, first dispersant DC, stabilizer, and photoinitiator is (65-75): (15-30): (1.0-5.0): (5.0-10.0): (0.5-1.5); The components of the nitride ceramic composite powder include nitride ceramic powder, surface modifier LMY and second dispersant DC; Wherein, the mass ratio of the nitride ceramic powder, the surface modifier LMY, and the second dispersant DC is (85-95): (5.0-10): (2.0-5.0).
2. The low viscosity photocurable nitride ceramic slurry according to claim 1, characterized in that: The photocurable nitride ceramic slurry is prepared by ball milling and mixing nitride ceramic composite powder, polyacrylate, first dispersant DC, stabilizer and photoinitiator in a mass ratio of (65-75): (15-30): (1.0-5.0): (5.0-10.0): (0.5-1.5); The nitride ceramic composite powder is prepared by mixing nitride ceramic powder, surface modifier LMY powder and second dispersant DC in a mass ratio of (85-95): (5.0-10): (2.0-5.0).
3. The low viscosity photocurable nitride ceramic slurry according to claim 1, characterized in that: The polyacrylate is a mixture of at least two of 1,6-hexanediol diacrylate, polysiloxane acrylate, trimethylolpropane triacrylate, and ditrimethylolpropane tetraacrylate in any proportion; The stabilizer is KH570; the photoinitiator is TPO.
4. The low viscosity photocurable nitride ceramic slurry according to claim 1, characterized in that: The particle size of the nitride ceramic powder is 0.5 to 5 μm; The first dispersant DC and the second dispersant DC are organic phosphates; The surface modifier LMY is a Li2O-Mg-Y2O3 ternary eutectic oxide, which is prepared by mixing lithium oxide, magnesium oxide, and yttrium oxide in a proportion to form a ternary eutectic oxide.
5. The low-viscosity photocurable nitride ceramic slurry according to claim 1, characterized in that: The preparation process of the surface modifier LMY is as follows: Weighing lithium oxide powder, magnesium oxide powder and yttrium oxide powder according to the eutectic ratio, added to an ethanol solvent, and stirred to obtain a mixture M; The mixture M is ball-milled to obtain a uniformly dispersed slurry; The ethanol solvent in the slurry is volatilized to obtain the surface modifier LMY in powder form.
6. The low viscosity photocurable nitride ceramic slurry according to claim 5, characterized in that: The ball milling treatment conditions are ball milling at a rate of 180 to 300 r / min for 6 to 10 hours; The ethanol solvent in the slurry is volatilized under normal temperature and atmospheric environment, or the ethanol solvent is evaporated and removed in an oven at 50 to 60° C. to obtain the surface modifier LMY in powder form.
7. A method for preparing the low-viscosity photocurable nitride ceramic slurry according to any one of claims 1 to 7, characterized in that: The following steps are involved: Weigh the raw material components according to the formula ratio, add the stabilizer, the first dispersant DC, and the photoinitiator to the polyacrylate in sequence while stirring, and stir and mix evenly to obtain a uniformly dispersed photosensitive resin system; Weighing nitride ceramic powder, surface modifier LMY powder, and second dispersant DC according to the formula mass ratio; adding nitride ceramic powder, surface modifier LMY powder, and second dispersant DC into ethanol solvent while stirring and dispersing them uniformly to obtain pre-dispersed slurry; evaporating the ethanol solvent in the pre-dispersed slurry to obtain ceramic powder; sieving the ceramic powder to obtain the nitride ceramic composite powder; Adding the nitride ceramic composite powder to the photosensitive resin system while stirring, stirring and dispersing evenly to obtain a preliminarily homogenized nitride ceramic slurry; The preliminarily homogenized nitride ceramic slurry is ball-milled to obtain the light-cured nitride ceramic slurry.
8. The method for preparing the low-viscosity photocurable nitride ceramic slurry according to claim 7, characterized in that: Weigh the raw material components according to the formula ratio, add the stabilizer, the first dispersant DC, and the photoinitiator to the polyacrylate in sequence while stirring, and stir and mix evenly for a stirring time of not less than 0.5h to obtain a uniformly dispersed photosensitive resin system; Weigh the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC according to the formula mass ratio; add the nitride ceramic powder, the surface modifier LMY powder and the second dispersant DC into the ethanol solvent while stirring, and stir at a rate of not less than 200 r / min for 2 to 4 hours to obtain a pre-dispersed slurry; evaporate the ethanol solvent in the pre-dispersed slurry at a heating temperature of 50 to 60° C. to obtain a ceramic powder; pass the ceramic powder through a 200-mesh sieve to obtain the nitride ceramic composite powder; Adding the nitride ceramic composite powder to the photosensitive resin system while stirring, stirring at a rate of not less than 100 r / min for 2 hours to obtain a preliminarily homogenized nitride ceramic slurry; The preliminarily homogenized nitride ceramic slurry is ball-milled at a rate of 200 to 300 r / min for 10 to 24 hours to obtain the light-cured nitride ceramic slurry.
9. Use of the photocurable nitride ceramic slurry according to any one of claims 1 to 6 in the preparation of AlN nitride ceramic parts, BN nitride ceramic parts, and Si3N4 nitride ceramic parts.
10. The use according to claim 9, characterized in that: In the process of preparing AlN nitride ceramic parts, BN nitride ceramic parts or Si3N4 nitride ceramic parts, a photocuring ultraviolet light source is used to photocure the photocuring nitride ceramic slurry to obtain a photocuring nitride ceramic body; and the photocuring nitride ceramic body is degreased and sintered in sequence to obtain a nitride ceramic part; The wavelength of the ultraviolet light source used for photocuring is 355-405 nm.
Citation Information
Patent Citations
Photo-cured silicon nitride ceramic slurry, silicon nitride ceramic and preparation method thereof
CN108892515A
Refractive index-matched additives for photo-curable compositions
CN109791373A
Aluminum nitride ceramic part and forming method thereof
CN117776734A
Transparent composite composition
EP2821436A1
Ceramic compact and its production
JP1994211560A
Cited By
Light-cured silicon nitride ceramic slurry, silicon nitride ceramic and preparation method thereof
CN122277262A
Photocurable silicon nitride ceramic slurry, silicon nitride ceramic and method for manufacturing the same
CN122277262B